Kemampuan Berpikir Kreatif Siswa SMP dalam Menyelesaikan Soal Matematika Open-Ended - Pakpahan, Milka Rosabella Marito; Wijayanti, Pradnyo (MATHEdunesa, 2025)
This study aims to describe the creative thinking ability of junior high school students in the aspects of fluency, flexibility, and novelty in solving open-ended mathematics problems. The subjects of the study were students of class VII-B at SMPN 3 Surabaya. Data was collected by examining the results of written tests based on indicators of creative thinking skills and conducting interviews. The question test is a creative thinking ability test for open-ended mathematics problems. Interviews in this study were conducted with 4 out of 30 students based on the results of the work of 30 students to explore more deeply the aspects of students’ creative thinking. Data analysis in this study used indicators of creative thinking skills, namely fluency, flexibility, and novelty. The results showed that the fluency aspect was demonstrated by 25 out of 30 students by showing various correct answers. The flexibility aspect was demonstrated by 3 out of 30 students by showing various alternative solutions, the various solutions in question mean using a combination of various concepts of mathematical material needed such as a combination of flat shape formulas with percentage comparisons, a combination of flat shape formulas with Pythagoras, and by conducting a sketch test of the shape. In terms of novelty, it was demonstrated by 1 out of 30 students by showing a diversity of answers and/or different ways of solving than the majority of students' answers in general.